Zonation pattern and carbon stock potential estimation between replanted and natural mangrove stand in selected barangays in Babatngon, Leyte - Delmonte, Jhon Patrick P.
Mangroves play a vital role in carbon sequestration. Moreover, while studies have shown that various environmental factors influence zonation patterns in mangrove ecosystems, it is unclear if the same pattern is observed in both naturally growing and replanted mangrove stands. This study aimed to compare the zonation pattern and the carbon stock potential of mangroves in natural and replanted sites in Babatngon, Leyte. Forty-eight 10 m x 10 m plots were established in 7 barangays and were systematically placed in both landward and seaward zones following the standard transect line-plot method. Aboveground and belowground biomass was estimated using allometric equation and these values were then converted to estimate its carbon stock potential. Floristic diversity of mangroves comprised 19 species of true and associated mangroves species, of which C. philippinense was found to be rare. Particularly, Acanthus, Acrostichum, Bruguiera, and Nypa fruticans species were found to inhabit the landward zones based on their abundance. Meanwhile, the seaward zone was dominated by S. alba, A. marina, and R. apiculata species. ANOVA revealed a significant difference between the abundance of species in natural stratum with A. corniculatum having significantly higher abundance than other species in this stratum. A significant difference between the abundance of species in the replanted stratum was also observed with R. apiculata having the highest abundance. Among the physico-chemical factors determined, only salinity showed significant correlation with species abundance in landward species (r=-0.853, p<0.01) which may indicate that it has influenced the mangrove zonation pattern in the stratum. Overall, the mean biomass was highest in the natural stratum (48.64 t/ha) compared to replanted (19.74 t/ha). C-stock potential was valued at 24.32 t/ha and 9.87 t/ha for natural and replanted respectively.